Trends in Violence in Scandinavia According to Different Indicators. An Exemplification of the Value of Swedish Hospital Data - Estrada, Felipe (The British journal of criminology, 2006)
In Scandinavia, as in many other parts of Europe, violence constitutes an important focus for the public and political debate on crime. Much of what is said in the public debate, and done in the field of criminal policy, stems from a perception that violence is on the increase. This paper presents a new social indicator of trends in violence - Swedish hospital admissions resulting from acts of violence - and evaluates this measure in the light of more traditional indicators of violence - crime statistics, victim surveys and homicide statistics. The hospital data comprise 90,000 admissions from the years 1974-2002. The results show that admissions caused by violence are more numerous in the 1970s and 1990s and fewer in the 1980s. Nothing in the hospital data indicates an increase in hospital admissions resulting from serious violent incidents over this period. No increase is noted in either fractures or knife and gunshot wounds. Thus, the continuous upward trend noted in crime statistics is not verified. Instead, the hospital data serve to verify the more stable trends indicated by victim surveys and lethal violence statistics